Dynamic analysis and design of a multipurpose lower limb exoskeleton for rehabilitation. (14th November 2022) - Li, Gang; Su, Qiying; Xi, Wenqiu; Song, Zhendong; Bao, Renren; Du, Zhenjun
To solve some defects of exoskeleton robot at present, this article establishes the dynamic model of human lower limb. The torque curves for hip joint and knee joint are obtained. A dynamics simulation is conducted in ADAMS which will guide the selection of motors and reducers for exoskeleton joints. Three structural design projects for leg and an integrated joint with the function of force perception are proposed. Then a lightweight exoskeleton is put forward and a kinematics simulation of man–machine coupling system is carried out in ADAMS. This article sets up a 24-V low-voltage control electrical system and a rehabilitation training expert system. Some performance tests and clinical experiments are carried out by an experimental prototype. The results show that the joints have sufficient driving torque. Leg structure has large adjustment range and self-locking function. The exoskeleton has lightweight and does not interfere with human body during movement. The expert system has a friendly operation interface and abundant functions. Clinical experimental results show that lower limb exoskeleton has good rehabilitation effect for some diseases.